2022
DOI: 10.1101/2022.07.10.499282
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemokine CXCL4 interactions with extracellular matrix proteoglycans mediate wide-spread non-receptor mediated immune cell recruitment

Abstract: Leukocyte recruitment from the vasculature into tissues is a crucial component of the immune system, but is also key to inflammatory disease. Chemokines are central to this process but have yet to be therapeutically targeted during inflammation, due to a lack of mechanistic understanding. Specifically, CXCL4 (PF4) has no established receptor that explains its function. Here we use biophysical, in vitro and in vivo techniques to determine the mechanism underlying CXCL4 mediated leukocyte recruitment. We demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Although it makes sense that weaker (less-specific) interactions will facilitate localization, particularly in the context of the bloodstream, certain chemokines (e.g., CXCL4 (PF4)) bind with incredibly high affinity. Recent work has suggested that some chemokines like CXCL4 primarily function by binding to GAGs, rather than directly to chemokine receptors (107). This can be mediated by signaling through cell surface proteoglycans and/or remodeling the ECM glycocalyx to facilitate leukocyte-endothelial interactions (108).…”
Section: Ecm Regulation By Chemokines and Cytokinesmentioning
confidence: 99%
“…Although it makes sense that weaker (less-specific) interactions will facilitate localization, particularly in the context of the bloodstream, certain chemokines (e.g., CXCL4 (PF4)) bind with incredibly high affinity. Recent work has suggested that some chemokines like CXCL4 primarily function by binding to GAGs, rather than directly to chemokine receptors (107). This can be mediated by signaling through cell surface proteoglycans and/or remodeling the ECM glycocalyx to facilitate leukocyte-endothelial interactions (108).…”
Section: Ecm Regulation By Chemokines and Cytokinesmentioning
confidence: 99%
“…GAG sulphation has previously been shown to drive interaction specificity with other chemokines, e.g., CCL2 and CXCL4( 17, 24 ). We, therefore, hypothesised that GAG sulphation points could produce further differentiation in binding to CXCL9, 10 or 11.…”
Section: Resultsmentioning
confidence: 99%
“…ECM GAGs are particularly present within the glycocalyx that lines the luminal endothelial surface within blood vessels but can also be found throughout tissues( 14 ). Chemokine:GAG interactions have been shown to be key for leukocyte recruitment in vivo as they facilitate endothelial retention of chemokines on the endothelium in the presence of blood flow( 15, 16 ) and in the case of CXCL4 may directly mediate its function( 17 ). However, specific comprehension of the role of chemokine:GAG interactions on the cell surface and within tissues in leukocyte recruitment is lacking.…”
Section: Introductionmentioning
confidence: 99%